Comparative evaluation of the influence of immediate versus delayed loading protocols of dental implants: A radiographic and clinical study - Kushaldeep; Amrit Tandan; Viram Upadhyaya; Mohit Raghuvanshi (Wolters Kluwer Medknow Publications, 2018)
Aim: Immediate loading protocol, in recent times, has gained popularity as it has not only shortened the treatment time but also resulted in enhanced patient satisfaction. The aim of this study was to evaluate and compare the effectiveness of immediate implant loading protocol over conventional implant loading protocol with respect to peri-implant bone loss. Materials and Methods: Twenty patients selected for this study were divided into two groups. In Group I patients, implants were immediately loaded, whereas in Group II, they were loaded with conventional loading protocol. Peri-implant bone loss was measured and compared using intraoral periapical radiographs with the grid at the time of implant loading, 1, 3, and 6 months after implant loading. Results: Change in radiographic bone loss in both the groups was found to be statistically significant when baseline was compared to 1, 3, and 6 months, but the difference in the bone loss between Group I and II was not found to be statistically significant. Conclusion: No statistically significant difference was observed in the crestal bone loss on comparison of immediate loading to delayed loading protocol. Clinical Significance: After achieving good primary stability, immediate-loaded implants can be used for the benefit of the patients as it reduces the period of edentulism.